Patterns of Alcohol Consumption and Adherence to Anti-Retroviral Therapy(ART) in patients with HIV - Musayón-Oblitas, Yesenia (2025)
Objective: To identify alcohol consumption patterns associated with adherence to anti-retroviral therapy (ART) among HIV-infected patients. Methods: A cross-sectional study was conduced among 4000 patients above 18 years of age who received ART through the Estrategia Sanitaria Nacional de Prevención y Control de ITS- VIH/SIDA from 2004 in one hospital in Lima. We randomly selected 351 patients and performed the analysis from September 2017 to January 2018. Alcohol consumption was evaluated by measuring intake at least once per life, in the last year, in the previous six months, last month, and in the last seven days. Adherence was measured using the Simplified Medication Adherence Questionnaire (SMAQ). Prevalence ratios were calculated. The Comité de Ética del Hospital Nacional Cayetano Heredia y de la Universidad Peruana Cayetano Heredia approved the study. Results: 74% were males; the mean age was 38 and 25% adhered to ART. An association between adherence and consumption in the last six months (p=0.017) and in the last month (p=0.011) with a prevalence rate of 1.158 (1.022<RP<1.312) and 1.167 (1.037<RP<1.312), respectively. Conclusion: Alcohol consumption in the last six and previous months is associated with lack of adherence to ART.